Pengaruh Strategi Produk Terhadap Pemasaran Produk PT. Pos Indonesia Cabang Tuhemberua - Laoli, Eka Septianti (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2020)
Pos Indonesia in increasing the marketing of its products by innovating with its products, especially in the digital market sector. The purpose of this study was to determine how much influence the product strategy has on product marketing. This study uses a quantitative calculation method with data collection techniques using a questionnaire. The population in this study were 32 people. The technique of taking sample members in this study is done by saturation sampling technique that is the technique of determining the sample if all members of the population are used as samples, because the total population is equal to the number of samples, the number of sample members is 32 people. The results of this study have a significant effect between product strategy on product marketing at PT. Pos Indonesia Branch Tuhemberua, North Nias Regency.